Study on operational and fleet utilisation / Sunan Muhdzir Jamil - Sunan Muhdzir, Jamil (Faculty of Business and Management, 1990)
Presently, Lori Malaysia Berhad is owned by Technivest Sendirian Berhad.. under the new management team, they have set up the task of improving the services to its clients as their prime objective.